PREPARATION OF PHTHALONITRILE MONOMER WITH LOW MELTING POINT - Botagoz M. Kaldybayeva,; Alisher Ye. Khussanov,; Arlan Zh. Abilmagzhanov,; Baurzhan N. Korganbayev,; Zhakhongir Ye. Khussanov,; Stanislav Boldyryev, (Academic Scientific Journal of Chemistry, 2020)
This article presents the results of the synthesis of para – and meta-hydroxyphenoxyphalonitrile, phosphorus-containing chlorangidrides with various substituents in phosphorus and 4-(3-propargyloxyphenoxy) phthalonitrile, the introduction of which into the binder, allowed to achieve the necessary viscosity indicators without loss of heat resistance. At the first stage, it was proposed to obtain a monomer with a phenoxy group in phosphorus. For this purpose, we proposed the use of dimethylacetamide (DMAA) with K2CO3, but the product was hydrolytically unstable in the main medium, so it was impossible to isolate the desired monomer. To solve this problem, we conducted a number of experiments on the selection of synthesis conditions using various solvents. Comparing the Tgt of the obtained monomers, we found higher values for para-oriented phthalonitriles, which is probably due to higher structure symmetry, as well as an increase in glass transition temperature (Tgt) for phosphonate-based monomers. Due to the equally high thermal properties of the cured matrices, we decided to use 4-(3-hydroxyphenoxy) phthalonitrile as the main precursor, as well as phosphate chlorangidrides. Based on the calculated data, a pattern was identified that consists in a decrease in the Tgt of phosphorus-containing phthalonitriles when switching to aliphatic substituents in phosphorus. A decrease in the Tgt of monomers was found with an increase in the size of the aliphatic substituent. As a result of the experiment, we obtained 9 new phosphoruscontaining phthalonitrile monomers with high yield that are resistant to hydrolysis, which is confirmed by the fact that the products were isolated by flash chromatography on silica gel, as well as two-dimensional TLC. The synthesized substances were glassy masses with Tgt = - 5-58 °C. The consistency of the approach involving the introduction of phosphate bridges into the structure of phthalonitriles was shown.